Developing partnerships: gender, sexuality, and the reformed World Bank - Bedford, Kate (University of Minnesota Press, 2009)
"A nuanced critique of how the World Bank encourages gender norms through its policies, Developing Partnerships argues that financial institutions are key players in the global enforcement of gender and family expectations.By combining analysis of documents produced and sponsored by the World Bank with interviews of World Bank staffers and case studies, Kate Bedford presents a detailed examination of gender and sexuality in the policies of the world's largest and most influential development institution. Looking concurrently at economic and gender policy, Bedford connects reform of markets to reform of masculinities, loan agreements for export promotion to pamphlets for indigenous adolescents advising daily genital bathing, and attempts to strengthen institutions after the Washington Consensus to efforts to promote loving couplehood in response to economic crisis. In doing so, she reveals the shifting relationships between development and sexuality and the ways in which gender policy impacts debates about the future of neoliberalism.Providing a multilayered account of how gender-aware policies are conceived and implemented by the World Bank, Developing Partnerships demonstrates as well how institutional practices shape development."-- Site de l'éditeur.
Keywords: LGBTQIA2+; approches et analyses; care; cours; discipline; discours dominant; histoire et politique; hétérosexisme; identités LGBTQIA2+; pol4022; premier cycle; ressource en ligne; science politique; science politique et droit; sciences de la gestion; sexisme; systèmes d'oppressions; thématiques; économie

From the 'woman's point of view' ten years later: Towards a feminist organization studies - Calas, Marta B.; Smircich, Linda (The Sage Handbook of Organization Studies, 2006)
Keywords: OFDIG; approches et analyses; discipline; femmes*; féminisme matérialiste; féminisme radical; genre; identités LGBTQIA2+; organisation; post-structuralisme; psychanalyse; ressource en ligne; sciences de la gestion; thématiques; économie

How (the meaning of) gender matters in political economy - Peterson, Spike V. (New Political Economy, 2005)
Keywords: OFDIG; approches et analyses; discipline; genre; identités LGBTQIA2+; inégalités; ressource en ligne; sciences de la gestion; systèmes d'oppressions; thématiques; économie

Social provisioning as a starting point for feminist economics - Power, Marilyn (Feminist Economics, 2004)
The past decade has seen a proliferation of writing by feminist economists. Feminist economists are not identified with one particular economic paradigm, yet some common methodological points seem to be emerging. I propose making these starting points more explicit so that they can be examined, critiqued, and built upon. I use the term “social provisioning” to describe this emerging methodology. Its five main components are: incorporation of caring and unpaid labor as fundamental economic activities; use of well-being as a measure of economic success; analysis of economic, political, and social processes and power relations; inclusion of ethical goals and values as an intrinsic part of the analysis; and interrogation of differences by class, race-ethnicity, and other factors. The paper then provides brief illustrations of the use of this methodology in analyses of US welfare reform, gender and development, and feminist ecological economics.
Keywords: OFDIG; approches et analyses; discipline; droits des femmes*; genre; identités LGBTQIA2+; méthodologie; point de vue situé; ressource en ligne; sciences de la gestion; thématiques; économie